2009
DOI: 10.1037/a0013090
|View full text |Cite
|
Sign up to set email alerts
|

Work stressors, role-based performance, and the moderating influence of organizational support.

Abstract: As a test of the 2-dimensional model of work stressors, the present study proposed differential relationships between challenge stressors and hindrance stressors and role-based performance, which were expected to be moderated by organizational support. In a sample of 215 employees across 61 offices of a state agency, the authors obtained a positive relationship between challenge stressors and role-based performance and a negative relationship between hindrance stressors and role-based performance. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
231
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(253 citation statements)
references
References 55 publications
15
231
3
4
Order By: Relevance
“…It has been suggested that individuals further categorize stressors as being either challenging, when they are perceived to be manageable, and thus presenting an opportunity for personal growth, or hindering, when they are perceived as constraining personal development (e.g., LePine, Podsakoff, & LePine, 2005;Wallace et al, 2009). While role ambiguity and conflict are typically considered to be hindrance stressors (e.g., LePine et al, 2005;Rodell & Judge, 2009), the situation is less clear with regards to role overload: Challenge stressor for some (e.g., McCauley, Rudennan, Ohlott, & Morrow, 1994), it is considered by others to be a hindrance stressor (e.g., LePine et al, 2005).…”
Section: Role Stressorsmentioning
confidence: 99%
“…It has been suggested that individuals further categorize stressors as being either challenging, when they are perceived to be manageable, and thus presenting an opportunity for personal growth, or hindering, when they are perceived as constraining personal development (e.g., LePine, Podsakoff, & LePine, 2005;Wallace et al, 2009). While role ambiguity and conflict are typically considered to be hindrance stressors (e.g., LePine et al, 2005;Rodell & Judge, 2009), the situation is less clear with regards to role overload: Challenge stressor for some (e.g., McCauley, Rudennan, Ohlott, & Morrow, 1994), it is considered by others to be a hindrance stressor (e.g., LePine et al, 2005).…”
Section: Role Stressorsmentioning
confidence: 99%
“…This could negatively affect their intrinsic motivation and work performance (Ryan & Deci, 2000). In such work settings, employees may try to cope with the situation by avoiding or exiting the political environment thus resulting in increased counterproductive and withdrawal behaviours, such as absenteeism and turnover intentions (Folkman & Lazarus, 1985;Rodell & Judge, 2009;Wallace, Edwards, Arnold, Frazier, & Finch, 2009). …”
Section: Behavioural Consequences Of Popmentioning
confidence: 99%
“…In the past, research studies used different variables as moderator between stressors and job outcomes, for example, organizational support (Wallace, Edwards, Arnold, Frazier, & Finch, 2009) and efficacy beliefs (Jex & Bliese, 1999) in Western culture. In the context of Pakistan, IWE have been used as moderator and resulted in strengthening the relationship of justice perceptions on job outcomes (Batool, Gul, & Shahzad, 2013;Khan, Abbas, Gul, & Raja, 2015;Sadozai, Marri, Zaman, Yousufzai, & Nas, 2013) but still there is lack of evidence which incorporates IWE as a moderator in relationship between stressors and job attitude.…”
Section: Introductionmentioning
confidence: 99%